IoT based garbage monitoring and management system - Hossain, Md. Noyeem; Rahman, Mahfujur (Review of Information Engineering and Applications, 2025)
Solid waste management has become an increasingly critical issue in Bangladeshi cities, particularly in major urban centers like Dhaka. Overflowing garbage bins are commonly observed, leading to unhygienic environments, pollution, and the spread of various diseases. To address this problem, an IoT-based Garbage Monitoring and Management System has been designed and implemented to enhance waste collection efficiency. This system enables real-time detection of waste levels in garbage bins. Using the Blynk application on smartphones, authorities can remotely monitor the status of each bin and take prompt action to empty them before they overflow, thereby reducing environmental pollution. Each bin is equipped with a microcontroller (ATMEGA328), an ultrasonic sensor, and a Wi-Fi module installed on the lid. When the bin reaches its full capacity, it sends a signal to the control center, notifying them of its status. Upon receiving the information via the Blynk application, authorities can direct the waste collection truck to empty the full bin promptly. This system can be implemented in any city to enhance garbage monitoring and management, ensuring a cleaner and healthier environment.